Eksplorasi Bakteri Endofitik Pemacu Tumbuh Asal Jaringan Tanaman Cabai Merah - Nuni Gofar (Jurnal Agrista, 2007)
Exploration of Growth Promoting Endophitic Bacteria Derived from Red Chilly TissuesABSTRACT. The aims of this research were: to explore growth promoting endophitic bacteria isolated from root of red chilly planted at swampy land, Ogan Ilir, South Sumatera, and to study the ability of resulted isolates to promote growth of red chilly by bioassay evaluation; and to evaluate the ability of resulted isolates to produce IAA in vitro. Different stage of red chilly as sources of endophitic bacteria samples were collected from various locations of chilly farms in Ogan Ilir District, South Sumatera. The results of this research proved that endophitic bacteria derived from root red chilly tissues acted as growth promoting, neutral and growth inhibiting bacteria. First, second and third of selection resulted in 8, 6, and 3 consortia of endophitic bacteria, which consistently promoted the growth of red chilly. The amount of IAA resulted by S248 isolates of endophitic bacteria (3.36 mg kg-1) as significantly lower than those of S348 isolates (4.16 mg kg-1) and S830 isolates (3.93 mg kg-1). The amount of IAA resulted by S348 isolates did not significantly differ from that of S830 isolates. Endophitic bacteria identified from S348 isolates were Pseudomonas aeruginosa and Bacillus cereus.